Bahasa Indonesia - dewi28, choirunnisa28 nirmala28 (Maliki Interdisciplinary Journal, 2025)
This research aims to understand the role of social media, innovation and identity exploration in shaping the dynamics of Gen Z's lives in the digital era. This research uses a descriptive qualitative approach based on interviews and literature reviews to show that social media functions as a forum for identity exploration and a means to produce innovation, but it also faces various challenges such as social pressure and complex information. These results show that understanding the relationship between these three dimensions is important for Gen Z to face social dynamics in the digital era. It is hoped that this research will provide insight for educators, media professionals and policy makers on how to support Gen Z in facing various changes.